(untitled) (Portuguese Journal of Family Medicine and General Practice, 2013)
Sweet’s Syndrome is a neutrophilic dermatosis. It is associated in 50% of cases with infectious, inflammatory, autoimmune, and neoplastic diseases (in 20-25% of cases). The aim of this presentation is to alert the family physician to this condition and to describe the findings necessary for the diagnosis. We report the case of a woman with flu-like symptoms of five days’ duration. Two days after the beginning of these complaints, she reported the sudden onset of circular skin lesions in the form of erythematous papules with central discoloration. She denied pruritus, but complained of tenderness of the lesions. After an initial evaluation, the patient was referred to a dermatologist, who performed a skin biopsy. The histopathological examination revealed a neutrophilic infiltration of the dermis, sparing vascular structures. The diagnosis of Sweet’s Syndrome was made and corticosteroid therapy was started, with complete resolution of the lesions in a few days. Initial testing for exclusion of an associated neoplasm was negative. The patient should perform a complete blood count every six months and cancer screening tests appropriate for her age and gender.